2018
DOI: 10.22159/ajpcr.2017.v11i1.22349
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of C1-C2 Sustained Natural Apophyseal Glide Combined With Dry Needling on Pressure Point Threshold and Headache Disability in Cervicogenic Headache.

Abstract: Objective: The main objective of this study was to evaluate the effectiveness of dry needling and mulligan C1-C2 sustained natural apophyseal glides (SNAGs) in increasing pressure point threshold and reducing headache disability in patients with CGH.Methods: This study was conducted on 150 patients. They were divided into three groups for the purpose of the study. Group A was referred to as the dry needling group. They were subjected to dry needling for treating the pain. Group B was the manual therapy group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, some studies have indicated that the SNAG technique is applied without using cervical rotation (9,10). According to the results of the current study, the SNAG technique should be applied with cervical rotation in the direction where movement is restricted.…”
Section: Rehabilitation In Cervicogenic Headachementioning
confidence: 66%
See 1 more Smart Citation
“…However, some studies have indicated that the SNAG technique is applied without using cervical rotation (9,10). According to the results of the current study, the SNAG technique should be applied with cervical rotation in the direction where movement is restricted.…”
Section: Rehabilitation In Cervicogenic Headachementioning
confidence: 66%
“…3 additional items were added to obtain detailed information about Mulligan mobilization. These questions were selected due to some differences in the techniques applied in studies on Mulligan mobilization for cervicogenic headache (9,10). One question asked whether Mulligan mobility has long-term effectiveness, and two questions were directed to the rotational component of Mulligan mobilization for cervicogenic headache.…”
Section: Participantsmentioning
confidence: 99%